De novo heterozygous missense and loss‐of‐function variants in CDC42BPB are associated with a neurodevelopmental phenotype. Issue 5 (7th February 2020) - Chilton, Ilana; Okur, Volkan; Vitiello, Giuseppina; Selicorni, Angelo; Mariani, Milena; Goldenberg, Alice; Husson, Thomas; Campion, Dominique; Lichtenbelt, Klaske D.; van Gassen, Koen; Steinraths, Michelle; Rice, Jennifer; et al.
Abstract: CDC42BPB encodes MRCKβ (myotonic dystrophy‐related Cdc42‐binding kinase beta), a serine/threonine protein kinase, and a downstream effector of CDC42, which has recently been associated with Takenouchi‐Kosaki syndrome, an autosomal dominant neurodevelopmental disorder. We identified 12 heterozygous predicted deleterious variants in CDC42BPB (9 missense, 2 frameshift, and 1 nonsense) in 14 unrelated individuals (confirmed de novo in 11/14) with neurodevelopmental disorders including developmental delay/intellectual disability, autism, hypotonia, and structural brain abnormalities including cerebellar vermis hypoplasia and agenesis/hypoplasia of the corpus callosum. The frameshift and nonsense variants in CDC42BPB are expected to be gene‐disrupting and lead to haploinsufficiency via nonsense‐mediated decay. All missense variants are located in highly conserved and functionally important protein domains/regions: 3 are found in the protein kinase domain, 2 are in the citron homology domain, and 4 in a 20‐amino acid sequence between 2 coiled‐coil regions, 2 of which are recurrent. Future studies will help to delineate the natural history and to elucidate the underlying biological mechanisms of the missense variants leading to the neurodevelopmental and behavioral phenotypes.